Educational Intervention on Knowledge, Attitudes, and Preventive Behaviors Toward Tuberculosis and Hypertension in Kelurahan Binaan - Badri, Putri Rizki Amalia; Artanto, Ardi; Asmalia, Resy; Anggina, Dientyah; Fitriani, Deska; Iskandar, Zhafirah; Yogustri, Adharia; Kurniati, Leni; Widyanti, Putri; Asri, Afina; Anzani, Tsabitah; Sulistiani, Taris; Larasati, Delvi; Sani, Regina; Yuvita, Uly; Taqiyah, Fakhriyah (Indonesia Berdaya, 2026)
Tuberculosis (TB) and hypertension remain major public health burdens in Indonesia, contributing to the country’s persistent double burden of disease. Community-based health promotion programs serve as a strategic approach to enhance awareness and preventive behaviors. This research aim to evaluate the effect of educational interventions on knowledge, attitudes, and preventive behaviors related to tuberculosis and hypertension under the Kelurahan Binaan. A pre–post interventional study was conducted among 83 adult participants selected using inclusion and exclusion criteria. Interventions included health education on TB and hypertension and dietary counseling delivered through lecture-based methods. Data on knowledge, attitudes, and preventive behaviors were collected using validated questionnaires. Wilcoxon Signed Rank and McNemar tests were applied for analysis. Significant improvements were observed in knowledge of tuberculosis (Z = –6.050; p 0.001) and hypertension (Z = –4.735; p 0.001). Attitudes toward TB (p = 0.012) and hypertension (p 0.001) also increased significantly. Preventive behavior significantly improved for both TB (Z = –3.632; p 0.001) and hypertension (p 0.001). Correlation analysis revealed significant associations between knowledge, attitudes, and preventive behaviors. Educational and dietary interventions effectively improved community knowledge, attitudes, and preventive behaviors toward tuberculosis and hypertension. Sustainable and continuous education programs are recommended to maintain these improvements.